2017
DOI: 10.1155/2017/1375158
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Estimation of Organic Matter Content in Arid Soil Using Vis-NIR Spectroscopy Preprocessed by Fractional Derivative

Abstract: Soil organic matter (SOM) content is an important index to measure the level of soil function and soil quality. However, conventional studies on estimation of SOM content concerned about the classic integer derivative of spectral data, while the fractional derivative information was ignored. In this research, a total of 103 soil samples were collected in the Ebinur Lake basin, Xinjiang Uighur Autonomous Region, China. After measuring the Vis-NIR (visible and near-infrared) spectroscopy and SOM content indoor, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 51 publications
0
16
0
1
Order By: Relevance
“…The application of derivatives is an ideal treatment in spectral analysis ( Viscarra Rossel, McGlynn & McBratney, 2006 ). The VIS–NIR reflectance was derivative-converted to reduce the influence of noise, amplify and reveal the greater spectral features ( Wang et al, 2017a ). The fractional derivative has expanded the theoretical concept of classic derivative, which has been successfully adopted in spectral data processing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of derivatives is an ideal treatment in spectral analysis ( Viscarra Rossel, McGlynn & McBratney, 2006 ). The VIS–NIR reflectance was derivative-converted to reduce the influence of noise, amplify and reveal the greater spectral features ( Wang et al, 2017a ). The fractional derivative has expanded the theoretical concept of classic derivative, which has been successfully adopted in spectral data processing.…”
Section: Methodsmentioning
confidence: 99%
“…However, the detection of spectral information via FD and SD with wider order intervals could, to some degree, result in the loss of spectral information. Some studies have demonstrated significant improvements on potential applications of the fractional derivative in various fields ( Chen, 2008 ; Wang et al, 2017a ; Wang et al, 2017c ; Zhang et al, 2016a ). With the narrower order interval, the fractional derivative expanded the theoretical concept of classic derivative.…”
Section: Introductionmentioning
confidence: 99%
“…The SOM content in the Ebinur Lake basin is low (near 2%). With SOM content of 2% as a boundary, that is, when SOM content exceeded 2%, the SOM played a principal role in masking out the spectral features, while the SOM content was less than 2%, it became less effective [ 46 , 52 , 53 ]. In the study, the soil clay content was divided into five groups: 0%–1% ( n = 46), 1%–2% ( n = 40), 2%–3% ( n = 8), 3%–4% ( n = 7), and >4% ( n = 2).…”
Section: Discussionmentioning
confidence: 99%
“…To exploit the potential information in the spectral data, the Grünwald-Letnikov's Fractional-Order Differential Equations (FDEs) with FOs ranging from 0 to 2 and stepped by 0.2 were also applied on the raw reflectance and the transformed data in this study. Wang et al [14] measured the visible and near-infrared (Vis-NIR) spectroscopy and soil organic matter (SOM) content of 103 soil samples collected in the Ebinur Lake basin, Xinjiang Uighur Autonomous Region, China, and employed the fractional derivative algorithm for pretreatment. Partial least squares regression (PLSR) was applied for model calibration in their study.…”
Section: Introductionmentioning
confidence: 99%